Pemanfaatan Aplikasi Pembelajaran Google Classroom dalam Pembelajaran Bahasa Inggris secara Daring Siswa SMP Muhammadiyah Serpong Tangerang Selatan - Pari Purnaningsih; Resti Isnaeni (Jurnal Informatika Universitas Pamulang, 2022)
During COVID-19, teaching and learning activities were carried out in online learning. One of the learning media used by a number of schools in these activities is application of video conference, Google Classroom. The use of this media is certainly very helpful for teachers in carrying out learning and it is easier for students to gain knowledge. This study aims to determine the planning of online English learning by using the Google Classroom application, the effectiveness of implementing online English learning by using the Google Classroom application and knowing the problems faced and how to solve them in online English learning by using the Google Classroom application in SMP Muhammadiyah Serpong, South Tangerang. This research was conducted through several stages, such as analyzing, compiling materials, collecting and processing data, and reporting research results. Google Classroom usage in online learning English  at SMP Muhammadiyah Serpong obtained quite effective results. The results of this study were produced from the average of data of the questionnaire given to the students of SMP Muhammadiyah Serpong.